Avaliação de fosfatos naturais usando ácido cítrico e ácido fórmico - Franco , Marcelo; Braga, José Mário; G Rios , João Nelson; Lima Thiébaut, José Tarcísio (Revista Ceres, 2025)
An experiment was carried out to evaluate the use of citric and formic acids in extracting available phosphorus from phosphate rocks. Natural phosphates from Araxá and Patos de Minas, Minas Gerais, Brazil, were first partially acidified with sulfuric, hydrochloric and phosphoric acids, each applied to samples at levels of 5, 15 and 25% (volume: weight), then treated with 2% citric or formic acid, each at levels of 1:100 (volume acid-fertilizer).